Methodology for 3D reconstruction of craniofacial structures and their use in the finite element method (2008)
This article describes the implementation of a methodology for 3D reconstruction of craniofacial anatomical structures made up of hard and soft tissues from biomedical images to be used in applications that involve the finite element method in bioengineering. The methodology begins with the development of a biomedical image processing software in DICOM (Digital Imaging Standard for Medical Images) format made in C language that provides the point cloud of the anatomical structure, from which the structures are constructed and optimized. surfaces that are finally those that make up a solid that can be exported to ANSYS 10.0r. This process was carried out using the geometric modeling software ProENGINEER WILDFIRE 3.0r and GID 8.0r. Structures such as jaw, temporal bone and some dental pieces were reconstructed satisfactorily, retaining their anatomical characteristics, obtaining a geometric model that allowed biomechanical simulations to be carried out using the finite element method in ANSYS 10.0r. The methodology implemented provided a greater capacity for detail in the geometric modeling of anatomical structures, and in turn made it possible to carry out a biomechanical application without incurring simplifications such as the omission of the spongy bone and the inadequate allocation of the mandibular mechanical properties, so that The quality of the results could be affected. Although the validation of the study was carried out from the action of an orthodontic device on the jaw, the methodology developed could be applied to the evaluation of other problems involving different anatomical structures.